2014
DOI: 10.11604/pamj.2014.19.40.4908
|View full text |Cite
|
Sign up to set email alerts
|

Expérience oto-rhino-laryngologique de l’hôpital marocain de campagne en Guinée Conakry

Abstract: Il s'agit d'une étude prospective et descriptive portant sur les patients admis en consultation d'oto-rhino-laryngologie, au sein de l'hôpital marocain médico-chirurgical de campagne, déployé en Guinée Conakry, du 24 février au 24 mai 2014. Les critères d'inclusion étaient l’âge, le sexe, le type et la localisation de l'affection. L'objectif de notre étude est d’établir un regroupement diagnostique et topographique des principales affections otorhinolaryngologiques rencontrées en Guinée Conakry. Ont été examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
6
1
Order By: Relevance
“…Topographically our results do not agree with those from Attifi H [12] and Njiffou N [11] that found that nasal sinus infections were the most common. But on the type of affection our results are much closer.…”
Section: Discussioncontrasting
confidence: 99%
“…Topographically our results do not agree with those from Attifi H [12] and Njiffou N [11] that found that nasal sinus infections were the most common. But on the type of affection our results are much closer.…”
Section: Discussioncontrasting
confidence: 99%
“…Otorhinolaryngological diseases or Ear, Nose and throat diseases (ENT) in sub-Saharan Africa are rich and varied. A study conducted in Guinea Conakry reported an incidence of ENTs about 8.14% in all multidisciplinary consultations [1]. Some studies concerning these conditions have demonstrated an incidence of 41% in children under 15 years in Nigeria [2] and 20% of ENT emergencies in patients under 15 years in Douala, Cameroon [3].…”
Section: Introductionmentioning
confidence: 99%
“…Njifou [2] reported extremes from 1 day to 86 years old, with a predominance of the age group of 16 to 40 years old accounting for 52.09%. Attifi et al [1], in Guinea reported an average age of 33 years old with extremes of 9 months to 73 years old and a predominance of conditions in the age group of 20 to 29 years old. Chronic nasal sinus diseases mainly affect young people, though literature reports age groups below ours.…”
Section: ) Sociodemographic Characteristicsmentioning
confidence: 98%
“…The management of the nasal cavities and sinuses diseases requires clinical and paraclinical specialties. Nasosinusitis pathologies are on top of the list of Otorhinolaryngology diseases [1] [2] and their prevalence varies from one country to another. They reached 37.98% in Guinea in 2014 [1] and 38.65% in Senegal in 2017 [3].…”
Section: Introductionmentioning
confidence: 99%